The Role of Social Support in Loneliness among Migrant Workers: A Mini Literature Review - Fath Yustia Hendrawan; Fuad Nashori (MOTIVA: JURNAL PSIKOLOGI, 2026)
Loneliness is one of today's global problems, which may cause serious problems, such as poor health, depression or even suicidal behavior. Migrant workers are vulnerable to experiencing loneliness as they relocate and adapt to a new cultural environment. Social support is a key predictor of loneliness and plays an important role in reducing feelings of loneliness. This study aims to summarize and analyze how social support influences loneliness in migrant workers. This study utilizes a mini literature review and follows Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines to optimize documentation by implementing clear guidelines to reduce bias and error. The Scopus and PubMed databases were selected for this study due to their extensive indexing and coverage. The results show that the experience of loneliness in migrant workers is influenced not only by the existence of social relationships but also by their qualitative characteristics, including emotional depth and perceived supportiveness. Family-based social support appears to be an important factor, while its impact remains ambivalent. Digital communication can compensate for limitations in face-to-face interactions and play a buffering role in reducing loneliness. These findings emphasize the importance of interventions that enhance social support to reduce loneliness among migrant workers.